Avaliação das configurações da cadeia reversa para a gestão de resíduos eletroeletrônicos no Brasil e das práticas favoráveis à economia circular - Correia, Auro de Jesus Cardoso (2021)
In the era of accelerated industrialization, the high production of electro-electronic equipment leads to the generation of large amounts of waste, which can cause imbalances to the environment. In this context, Circular Economy is applied, which proposes the concept of avoiding waste, seeking to minimize the consumption of natural resources, the reuse of waste and the application of an economic system based on material circularity. In this scenario, the United Nations Agenda 2030 (of which Brazil is a signatory) highlights the need for the development of organizational practices in waste management as one of the purposes to promote the Circular Economy. Absences in literature concerning the identification of the most adequate configuration for the management of the e-waste reverse chain in Brazil and its respective practices that favor the Circular Economy, in addition to the direction of the recycled material and the practical application of the '4Rs' of the Circular Economy, characterize the gaps in this research. Thus, the objective of this study is to identify the most suitable configuration for the management of the electro-electronic waste reverse chain in Brazil and its respective practices favorable to the Circular Economy, in addition to the direction of the recycled material and the practical application. of the '4Rs' of the Circular Economy. The research method used in the study was the Survey. The results revealed that the most suitable configuration to promote Circular Economy in Brazil, refers to the 'Collective Management' and the recycled material is directed to the 'Secondary Market'. As far as the '4Rs' of Circular Economy are concerned, only the 'R' Recycle and the 'R' Remanufacturing are applied in this reverse chain. For the results attributed to the thirteen practices, which influence the management of the reverse chain to promote the Circular Economy in Brazil, the most representative made reference to legislations and regulations, and the effective participation of the consumer, followed by the management of outsourced companies for recycling, in addition to the insertion of logistic operators and treatment and recycling strategies. For the least representative factors, simulations and optimization strategies for logistical transportation, collection centers and recycling centers were highlighted.